Introduction - Ariate Jr., Joel F.; Reyes, Miguel Paolo P.; Del Mundo, Larah Vinda (Kasarinlan: Philippine Journal of Third World Studies; Vol 37 (2022): Marcos Lies, 2024)
Introduction of the book/ Kasarinlan special issue Marcos Lies .